Developing Critical Thinking and Social Awareness through Contextual Learning and Social Transformation: A Systematic Review - Ramadhan, Nabil Auliya; Anggraini, Septiana; Madhakomala, R. (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to systematically review the literature on the development of critical thinking and social awareness through contextual and transformative learning approaches. The urgency of this study arises from the increasing complexity of global social and environmental challenges, which demand that education go beyond academic achievement to include the formation of reflective, empathetic, and empowered learners. The research employs a Systematic Literature Review (SLR) method based on the PRISMA 2020 protocol. Data were collected from 13 empirical research articles published between 2010 and 2025 that met the inclusion criteria. Data analysis was conducted using thematic synthesis to identify patterns and key findings across the studies. The results indicate that project-based learning, critical reflection, the integration of local wisdom, and dialogical pedagogy are consistently effective in enhancing students' critical thinking and social awareness. Transformative learning that emphasizes multicultural values, social justice, and active participation also proves to foster empathy, tolerance, and civic responsibility. In conclusion, contemporary education must shift from a knowledge transmission model toward a more humanistic, participatory, and contextual approach. This study recommends strengthening teacher capacity, implementing adaptive curriculum design, and encouraging institutional innovation as key success factors in realizing effective transformative contextual learning.